Hyperpyrexia in a previously healthy pregnant female with COVID pneumonia: a case report and review of the literature - Nipun Lakshitha de Silva; Amitha Fernando; Rohini Wadanambi; A. R. J. P Niyas; Nihal Munasinghe; Gnani Somasundaram (Journal of Medical Case Reports, 2023)
Abstract Background Infection due to the SARS-CoV-2 virus can have a wide range of presentations from asymptomatic/mildly symptomatic to severe disease with multiorgan failure. Fever is a common symptom. But hyperpyrexia defined as temperature > 41.5 °C is not usual in COVID-19. Case presentation A 24-year-old previously well Sri Lankan female in the 24th week of gestation of her first pregnancy presented with fever and shortness of breath. She was confirmed to have coronavirus disease-2019 (COVID-19). History was suggestive of late presentation on approximately the eighth day of the illness. She had rapidly deteriorating hypoxia due to COVID pneumonia requiring mechanical ventilation two days after the admission. There was evidence of cytokine storm without any secondary bacterial infection. She received glucocorticoids, tocilizumab, and intravenous antibiotics. Although she initially showed mild improvements, she subsequently developed high-grade fever with the axillary temperature rising to 41.7 °C starting from the seventh day of admission. There were no causative medicines or risk factors to explain hyperpyrexia. She died on the ninth day of admission. Conclusions There are no reports of patients developing this complication during pregnancy. The pathophysiology of this rare life-threatening complication remains elusive. Detailed reporting and in-depth analysis of such patients will facilitate the understanding of the associations and successful management of these patients.